Sequencing, biochemical characterization, crystal structure and molecular dynamics of cellobiohydrolase Cel7A from Geotrichum candidum 3C. (8th October 2015) - Borisova, Anna S.; Eneyskaya, Elena V.; Bobrov, Kirill S.; Jana, Suvamay; Logachev, Anton; Polev, Dmitrii E.; Lapidus, Alla L.; Ibatullin, Farid M.; Saleem, Umair; Sandgren, Mats; Payne, Christina M.; Kulminskaya, Anna A.; et al.
Abstract : The ascomycete Geotrichum candidum is a versatile and efficient decay fungus that is involved, for example, in biodeterioration of compact discs; notably, the 3C strain was previously shown to degrade filter paper and cotton more efficiently than several industrial enzyme preparations. Glycoside hydrolase (GH) family 7 cellobiohydrolases (CBHs) are the primary constituents of industrial cellulase cocktails employed in biomass conversion, and feature tunnel‐enclosed active sites that enable processive hydrolytic cleavage of cellulose chains. Understanding the structure–function relationships defining the activity and stability of GH7 CBHs is thus of keen interest. Accordingly, we report the comprehensive characterization of the GH7 CBH secreted by G. candidum ( Gca Cel7A). The bimodular cellulase consists of a family 1 cellulose‐binding module (CBM) and linker connected to a GH7 catalytic domain that shares 64% sequence identity with the archetypal industrial GH7 CBH of Hypocrea jecorina ( Hje Cel7A). Gca Cel7A shows activity on Avicel cellulose similar to Hje Cel7A, with less product inhibition, but has a lower temperature optimum (50 °C versus 60–65 °C, respectively). Five crystal structures, with and without bound thio‐oligosaccharides, show conformational diversity of tunnel‐enclosing loops, including a form with partial tunnel collapse at subsite –4 not reported previously in GH7. Also, the first O‐ glycosylation site in a GH7 crystal structure is reported – on a loop where the glycan probably influences loop contacts across the active site and interactions with the cellulose surface. The Gca Cel7A structures indicate higher loop flexibility than Hje Cel7A, in accordance with sequence modifications. However, Gca Cel7A retains small fluctuations in molecular simulations, suggesting high processivity and low endo‐initiation probability, similar to Hje Cel7A. Database: Structural data are available in the Protein Data Bank under the accession numbers5AMP, 4ZZV, 4ZZW, 4ZZT, and4ZZU . The Geotrichum candidum GH family 7 cellobiohydrolase nucleotide sequence is available in GenBank under accession numberKJ958925 . Enzymes: Glycoside hydrolase family 7 reducing end acting cellobiohydrolase Abstract : We report the characterization of the GH7 CBH secreted by ascomycete G. candidum ( Gca Cel7A). X‐ray data revealed the first O- glycosylation in a GH7 crystal structure on a loop where the glycan influences loop contacts and interactions with the cellulose surface. Even though Gca Cel7A structures indicate higher loop flexibility than H. jecorina Cel7A, molecular simulations suggest high processivity and low endo‐initiation probability similar to Hje Cel7A.